2009
DOI: 10.1021/ja902629y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gold Adatoms and Stereochemistry in Self-Assembly of Methylthiolate on Au(111)

Abstract: On the basis of high resolution STM images and DFT modeling, we have resolved low- and high-coverage structures of methylthiolate (CH(3)S) self-assembled on the Au(111) surface. The key new finding is that the building block of all these structures has the same stoichiometry of two thiolate species joined by a gold adatom. The self-arrangement of the methylthiolate-adatom complexes on the surface depends critically on their stereochemical properties. Variations of the latter can produce local ordering of adato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
257
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(294 citation statements)
references
References 30 publications
31
257
2
4
Order By: Relevance
“…We note that the results from the core-level spectroscopy conform to the energetic argument in the preference for the MeS-Au-SMe structure over alternative adsorption models. 22 It is also consistent with experimental STM, 23 IR, 24 GIXRD, 25 and NEXAFS ͑Ref. 26͒ data.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We note that the results from the core-level spectroscopy conform to the energetic argument in the preference for the MeS-Au-SMe structure over alternative adsorption models. 22 It is also consistent with experimental STM, 23 IR, 24 GIXRD, 25 and NEXAFS ͑Ref. 26͒ data.…”
Section: Discussionsupporting
confidence: 77%
“…22 Although there is an uncertainty concerning the ability of state-of-the-art DFT methods to predict small energy differences ͓in particular, for reconstructed RS / Au͑111͒ systems, as the cohesive energy of gold is underestimated by ϳ15%͔ the structure based on RS-Au-RS units is consistent with the bulk of experimental data. RS-Au-SR complexes bonded to Au͑111͒ has been observed at different coverages by STM, 23 calculations of the infrared ͑IR͒ vibrational signatures match the experimental data, 24 simulations of the GIXRD maps 25 are in agreement with experiments and calculations for the RS-Au-RS structure compare favorably with sulfur K-edge near-edge x-ray absorption fine-structure ͑NEXAFS͒ measurement. 26 It has also been suggested that the RS-Au-RS structure might be consistent with normal-incidence XSW data.…”
Section: Introductionsupporting
confidence: 70%
“…Alkanethiols on Au(111) form clusters with Au atoms that can be described as M(SR) 2 , where R is an alkyl group. [9][10][11][12] These are analogous to MS 2 . On Ni(111), a triangular Ni 3 S 3 cluster has been identified, although its role in coarsening was not studied.…”
Section: Introductionmentioning
confidence: 95%
“…19,21,22 The same configuration, including Au adatoms bonded to two RS-groups, has been named the "standard model" for close-packed methylthiolate self-assembled monolayers on Au(111), 23 as it has been found in several experimental and theoretical studies for this system. [24][25][26][27] Such bonds between two S atoms and a Au adatom appear due to low reactivity of Au atoms in the close-packed (111) surface, and are expected to be less likely in stepped or kinked surfaces, where undercoordinated Au atoms form significantly stronger bonds to S. Moreover, the strong steric repulsions associated with adsorption of longer molecules will result in grafting densities of the order of 1 nm −2 or less, 28 where it is unlikely that thiolate groups from two different molecules will bind to the same Au atom.…”
Section: Introductionmentioning
confidence: 99%